Mathematics literacy skills in pre-service teachers: What could they do? - Istiandaru, Afit; Prasetyo, Puguh Wahyu; Istihapsari, Vita (Bulletin of Applied Mathematics and Mathematics Education, 2021)
Mathematics literacy is individual capacity to formulate, to employ, and to interpret mathematics in various contexts. Indonesian students aged 15 are required to perform these three skills and these abilities reflect the success of the curriculum. The results, however, are never considered satisfying since, many argue, the students are not accustomed to deal with the mathematics literacy problems. Teacher is then the one who takes the responsibility to make the students familiar with the literacy problems. This research aims to look closer at the mathematics literacy skills possessed by pre-service teachers. It is a qualitative research which involved 128 undergraduate student teachers as the subjects. A custom mathematics literacy test was developed with various contexts to measure the student teachers’ literacy skills according to the PISA framework. The results suggest that they performed well in the level 1 to 3 problems, but not in the level 4 to 6. Many errors made by the student teachers in the stage of formulating, employing, or interpreting. Finally, teachers need to be accustomed to this skill before they are ready enough to teach their students.